The Effectiveness of Spiritual Emotional Freedom Technique (SEFT) on Chest Pain in Patients with ST-Elevation Myocardial Infarction: A Quasi-Experimental Study - Fachrizal, Fachrizal; Marlina, Marlina; Syarif, Hilman (Rifa'Institute, 2025)
Introduction: Spiritual emotional freedom technique (SEFT) is a non-pharmacological intervention that combines spiritual, emotional, and physical aspects through tapping techniques at the body's meridian points to create relaxation and reduce stress. This study aims to analyze the effectiveness of SEFT on chest pain in ST-Segment Elevation Myocardial Infarction (STEMI) patients at dr. Zainoel Abidin Regional General Hospital Banda Aceh. Method: This study was a quasi-experiment with pretest-posttest control group design, namely the intervention group and the control group consisting of 17 respondents each. Results and Discussion: The results of the analysis using the wilcoxon Signed-Rank test showed that there was a statistically significant difference in chest pain p=0.001 after the intervention. The analysis of the Mann-Whitney U-test on chest pain also showed a significant difference of p=0.045. These results suggest that SEFT interventions contribute to lowering the physiological response of stress and pain perception in STEMI patients. Conclusions: SEFT is effective in lowering chest pain in STEMI patients, which shows an increased relaxation response of the body so that this technique can be used as a holistic nursing approach. For health workers, especially nurses, the SEFT technique can be an alternative to non-pharmacological interventions that are easy to apply.